Apocalyptic features of political discourses about the pandemic - Galofaro, Francesco (Revista Acta Semiotica, 2021)
Plan : Introduction 1. The apocalyptic thematic 2. Prophecy in two opposite political discourses 3. The pandemic between accident and explosion 4. Apocalypse vs Exodus 5. Programmed futures Conclusion